Diving into the unknown: fourteen new species of haplosclerid sponges (Demospongiae: Haplosclerida) revealed along the Peruvian coast (Southeastern Pacific) - Bispo, André; Willenz, Philippe; Hajdu, Eduardo (Zootaxa, 2022)
The Peruvian coast is certainly one of the poorest studied areas in the world for marine sponges biodiversity, with only 20 species registered so far from over 2,400 km coastline. In spite of its great species richness worldwide, there is not a single record of Haplosclerida in Peru. Accordingly, in this study we aimed to describe the species belonging to this order present in the relatively recent collections undertaken along the Peruvian coast by two of us (PhW, EH). Here, we describe fourteen new species, provisionally endemic to the Peruvian coast. This finding represents a major addition to the knowledge of the biodiversity of sponges along the Peruvian coast, increasing the list of species known to occur in this area by about 68%. This is also the largest single proposal of new Haplosclerida in over 37 years of sponge taxonomy worldwide. Niphates is for the first time recorded in the Southeastern Pacific, and an identification key to the Haplosclerida from the Peruvian coast is provided. Regarding the distribution of the described species, most of them—except for Chalinula chelysa sp. nov.—have a narrow geographic range, which might indicate their rarity or that the haplosclerid fauna in Peru is still poorly known.